Efektivitas Penilaian Kinerja Kepala Sekolah Sebagai Dasar Melakukan Promosi Kepala Sekolah SMA Negeri Di Kabupaten Karawang - Nurhalimatussadiah, Kiki; Faizin, Muhamad; Fahmi, Ilham (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to describe the effectiveness of the process of appointing school principals in SMA Negeri Karawang regency in the process of appointment and assessment in leading the school. The principal is the highest leader in the school. In the process of appointing a school principal, there are requirements and other provisions that already exist in government regulations. The service branch office under the auspices of the West Java Provincial Education Office is very concerned about teachers who will nominate to become school principals. The existence of certain rules and conditions will form a school that has quality education. Apart from having to fulfill the five personality competencies, of course, the principal's performance assessment is also purely based on the results of PKKS, Questionnaire 360, and Preview Scores. The research location this time was carried out at the Regional IV Service Branch Office in Purwakarta using a descriptive qualitative research method. The technique used for data collection is using interview, observation and documentation methods. The results of the study show that: (1) Principals at SMA Negeri Karawang Regency have met the criteria and requirements according to the rules that have been set. (2) in the process of appointing the position of the Principal, of course, he will be promoted to a school that has superior accreditation. (3) school principals must have five competencies such as Managerial, Supervision, Entrepreneurship, Personality and Social Competence. The method used in this research is Descriptive Qualitative Approach. Data collection techniques are carried out by means of observation, interviews and documentation. Data analysis techniques from this study are data reduction, data presentation and conclusion.